Marketing strategies of the family business CONSTRUNICA compared to similar companies in the city of Estelí, Nicaragua. Period 2018-2019 (Revista Científica Estelí, 2020)
This research aims to analyze the marketing strategies implemented by the family business CONSTRUNICA in order to design a strategy that allows them to increase the sales volume of their products. This is a quantitative research, because it analyses the relationship between two variables: marketing strategies and positioning of the company CONSTRUNICA compared with similar companies which distribute building materials in Estelí city. The data collection techniques used are surveys and interviews which were applied to the owners or managers of companies and customers. The main founding show that the strategies most used by the companies are: customer service, low prices, variety of brands and products, offers, discounts, home delivery, custom-made product, these strategies are those that have kept these companies on the market. New strategies are proposed to improve competitiveness, such as: 1) Offer quality products at comfortable prices for the acquisition of new customers, 2) Online training, 3) Advice from product suppliers for a better customer experience, 4) promotions for attracting new potential customers, 5) Acquisition of trucks for customer service, 6) advertising of products and materials, 7) expansion to other parts of the country.
Keywords: family business; marketing; competitiveness; positioning; customers